Elective stenting for symptomatic middle cerebral artery stenosis presenting as transient ischaemic deficits or stroke attacks: short term arteriographical and clinical outcome. Issue 6 (14th May 2004) - Kim, J K; Ahn, J Y; Lee, B H; Chung, Y S; Chung, S S; Kim, O J; Kim, W C; Joo, J Y
Abstract : Background: Although stent assisted angioplasty is an effective treatment for coronary and peripheral arterial disease, its efficacy in intracranial arteriosclerotic disease has not been verified. Objectives: To assess the radiographic and clinical outcome of stent assisted angioplasty for symptomatic middle cerebral artery (MCA) stenosis. Methods: We attempted stent assisted angioplasty in 14 patients with symptomatic high grade stenosis (>60%) on the proximal portion of the MCA, who had experienced either recurrent transient ischaemic attacks (TIAs) resistant to medical therapy or one or more stroke attacks. Patient records were analysed for angiographic characteristics, degree of stenosis, pre-procedural regimen of anti-platelet and/or anti-coagulation agents, use of devices, procedure related complications, pre-operative and post-operative single photon emission computed tomography (SPECT) findings, and clinical and radiographic outcomes. Results: Stent assisted angioplasty was successfully performed in 8 of 14 patients without any serious complications and unsuccessful in 2 of 14 patients due to the tortuous curve of the internal carotid artery siphon. Four patients had complications. Two patients had an arterial rupture; one patient was rescued by an additional stent and balloon tamponade, the other patient died. Complications in the other two patients included thrombotic occlusion and distal thrombosis. Residual stenosis was less than 50% in diameter in all the patients. All eight patients who underwent follow up cerebral angiography had no restenosis. Follow up SPECT showed improved perfusion in the affected MCA territory in all the tested patients with TIA and in one of three stroke patients. Using the modified Rankin Scale at follow up, four of five TIA patients and five of six stroke patients were assessed as functionally improved or having a stable clinical status. Conclusion: Although the re-stenosis rate in stent assisted angioplasty seems to be better than in primary balloon angioplasty as reported previously, the complication rate is still high. Elective stenting is an alternative therapeutic method for the prevention of secondary ischaemic stroke in stroke patients with MCA stenosis, and seems to be a potentially effective but also hazardous therapeutic technique in patients with recurrent TIAs. This study indicates the need for randomised control trial data of this intervention. Additionally, long term follow up data and additional clinical experience are required to assess the durability of this procedure.